Combination of Neurofibromatosis Type 1 and Type 1 Diabetes in an Adolescent - Babii, Serhii; Burlaka, Ievgeniia (The Ukrainian Scientific Medical Youth Journal, 2026)
neurofibromatosis type 1 (NF1, Recklinghausen disease) is an autosomal dominant neurocutaneous disorder. Main clinical signs include multisystem involvement, i.e. cutaneous, neurological, vascular and endocrine manifestations. Type 1 diabetes (T1D) is an autoimmune disease resulting in absolute insulin deficiency leading to the long-term metabolic and vascular complications. The coexistence of NF1 and T1D is rare in pediatric practice. The parallel course of these two diseases may aggravate metabolic instability, complicate differential diagnosis of neurological and cardiovascular manifestations. The latter require multidiscipline management. We present a clinical case of a 17-year-old adolescent female with genetically confirmed NF1 and a T1D. Disease course characterized by low glycemic control, diabetic polyneuropathy and early signs of secondary metabolic cardiomyopathy. Analysis of clinical, laboratory and instrumental evaluation revealed features of peripheral neuropathy, subclinical myocardial dysfunction and vascular dysregulation upon the absence of overt organ failure. The coexistence of NF1-related neurological and vascular abnormalities with T1D-associated microvascular and metabolic changes have diagnostic and therapeutic challenges. This case highlights the inter-related effects of NF1 and T1D on the nervous and cardiovascular systems. This in turn emphasize the importance of careful differential diagnosis of neuropathic symptoms and early detection of subclinical complications. The report highlights the need for long-term multidisciplinary follow-up involving endocrinologist, neurologist, cardiologist and genetic specialist. Finally, our case illustrates the importance of individualized management strategies, early screening for organ involvement and proactive prevention of complications in adolescents with combined genetic and autoimmune diseases.